Differential proteomic analysis of Acidithiobacillus ferrooxidans cells maintained in contact with bornite or chalcopyrite: Proteins involved with the early bacterial response - Felicio, Ana Paula [UNESP]; de Oliveira, Eliandre; Antonia Odena, Maria; Garcia, Oswaldo [UNESP]; Bertolini, Maria Celia [UNESP]; Caldas Ferraz, Lucio Fabio; Mariscal Ottoboni, Laura Maria; Marques Novo, Maria Teresa (Elsevier B.V., 2011)
Acidithiobacillus ferrooxidans is a chemoautotrophic bacterium capable of oxidizing ferrous iron or sulfides to obtain energy. Bornite and chalcopyrite are copper sulfides containing iron that present different susceptibilities to the bioleaching process. Here, the early bacterial response to these minerals was investigated using a differential proteomic approach. The protein profiles of cells kept in contact with bornite or chalcopyrite for 24 or 48 h were compared to that of cells not exposed to the minerals. Response to bornite exposure involved thirteen proteins, mainly related to energy metabolism, detoxification and protein synthesis. We detected increases in the expression levels of the proteins chaperonin, antioxidant and aldehyde dehydrogenase, as well as decreases in the expression levels of the proteins radical SAM domain, fructose-1,6-bisphosphatase, PfkB domain, heat shock HslVU. ribulose bisphosphate carboxylase and ribosomal proteins. Chalcopyrite contact led to a distinct metabolic response of the bacterium, since no significant alteration in the level of protein expression was detected. These findings could help to understand the metabolic impact in A. ferrooxidans after the initial addition of the cells to bornite or chalcopyrite during bioleaching processes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Acidithiobacillus ferrooxidans; Bornite; Chalcopyrite; Bioleaching; Proteomic analysis; Mass spectrometry